Ḥafṣa and al-Muṣḥaf: Women and the Written Qurʾān in the Early Centuries of Islam - Silzell, Sharon (Hawwa, 2015)
This study examines the ways male medieval Muslim writers portrayed Ḥafṣa bt. ʿUmar b. al-Khaṭṭāb (d. 45/665) and other seventh-century women and their roles as authorities and authenticators of the written word of God. By tracing Ḥafṣa’s ownership of the first complete written copy of the Muslim scripture, I identify the late third/ninth and fourth/tenth centuries as a period of conflict over the chain of transmission of the first Qurʾān. I argue that late third/ninth and fourth/tenth-century accounts of the collection and codification of the Qurʾān illustrate a conscious rewriting of Ḥafṣa’s role in those projects. I suggest that Ḥafṣa’s literacy may have been deemed a threat to the authenticity of the Qurʾān collected by Abū Bakr, resulting in a scholarly attempt to sever her from the codification project.